The Impact of Pediococcus acidilactici BK01 Supplementation on Production Performance and Quality of Japanese Quail Eggs - Ade Rakhmadi; Ade Sukma; Indri Juliyarsi; Sri Melia; Ely Febriyanti; Rizki Dwi Setiawan (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Probiotic supplementation in feed is currently under extensive research and development, particularly to improve egg production performance and enhance the quality of quail eggs. This study aimed to determine the effects of Pediococcus acidilactici BK01 supplementation on production performance, weight, fat, and cholesterol content of Japanese quail (Coturnix japonica) eggs. This study used four treatments and probiotic supplementation was performed using drinking water at four different concentrations (0, 1, 2, 3%). The supplementation of Pediococcus acidilactici BK01 demonstrated a significant difference (P<0.05) in both egg production and cholesterol content, yet did not yield a significant difference (P>0.05) in egg weight and lipid content. Pediococcus acidilactici BK01 supplementation at concentrations of 2% and 3% resulted in an increase in egg production from 60.85% to 84.52% and led to a reduction in cholesterol content by more than 50% (from 215.43 to 98.57 mg/dL) compared to the control group. Consequently, the administration of the probiotic Pediococcus acidilactici BK01 up to a concentration of 3% influenced on egg production and egg cholesterol content in Japanese quail.